Effect of vitamin D supplementation on motor symptoms in Parkinson’s disease: a meta-analysis of randomized controlled trials - Xu, Jing; Li, Jia; Sun, Ya-juan; Quan, Wei; Qin, Yi-dan; Song, Jia; Chen, Jia-jun (Frontiers in Nutrition, 2025)
IntroductionLower serum vitamin D levels may associate with higher motor symptom severity in Parkinson’s disease (PD). This study aimed to test the efficacy of supplemental vitamin D on ameliorating motor symptoms in PD, which is the most comprehensive study to assess the relationship between vitamin D supplementation and PD motor symptoms to date.MethodsAn electronic literature search supplemented by hand searching up to Sep 2024 identified 8 randomized controlled trials involving 646 cases of PD. Weighted mean difference (WMD) and 95% confidence interval (CI) of PD were assessed through pooling the collected data from eligible studies using Stata software.ResultsThe results indicated that supplemental vitamin D did not reduce the Unified Parkinson’s Disease Rating Scale part III score (WMD=-0.56, 95% CI=[-2.34, 1.23]), 10/8 m walk test time (WMD=0.59, 95% CI=[-0.46, 1.64]) and timed up and go (TUG) test time (WMD=-0.57, 95% CI=[-1.45, 0.31]). A statistically significant benefit of supplemental vitamin D was observed on 6-Minute walking test distance (WMD=24.85, 95% CI=[6.54, 43.16]).DiscussionThis meta-analysis suggested that supplemental vitamin D may extend 6-Minute walking test distance, improve partial motor symptoms. Vitamin D supplementation may play an active inhibitory role in the mechanisms of the development of PD